Nicotine replacement therapy decision based on modified intuitionistic fuzzy analytic hierarchy process / Norfazillah Matmali - Matmali, Norfazillah (2018)
The increasing population of smokers is a critical issue in developing countries in this century due to the fact that it is the major cause of preventable illness and alarming tobacco-related death. In dealing with this issue, the Nicotine Replacement Therapy (NRT) as a smoking cessation was introduced as part of the program to decrease the population of smokers. Due to the current situation, NRT selection faces difficulty to help smokers (patients) get rid of the smoking habit besides the many advantages of NRT. The NRT decision-making problem involves information dataset but there are not many research studies about NRT decision based on multi-criteria decisionmaking (MCDM) to help decision makers such as patient (smokers), medical officer and pharmacist in the decision-making process. In response to this problem, a systematic MCDM process is required in this situation to evaluate the decisionmaking problem for NRT which involves both quantitative and qualitative information dataset in order to gain more comprehensive results. Besides that, the advantages of the intuitionistic fuzzy set (IFs) are utilized to handle fuzziness, uncertainty in decision-making and vagueness of information due to human language and subjectivity of the problem. In this research, the Modified Intuitionistic Fuzzy Analytic Hierarchy Process (IF-AHP) method was utilised to gain more systematic, comprehensive, and able to deal with uncertainty in the decision-making process. A case study was conducted at the Queen Elizabeth Hospital, Kota Kinabalu, Sabah which is patient, medical officer and pharmacist as respondent in order to demonstrate the feasibility of the proposed model when dealing with uncertainty. The proposed model was well suited with the local context and complied with the validating analysis in NRT decision-making problem. The result of this research shows that the best NRT alternative is gum, followed by lozenge, inhaler and patch which identified based on the local context. In addition, the IF-AHP method in this study is applicable as a specific decision tool for NRT decision-making problem. The result also shows that the proposed method gained a positive outcome with effect of changing the parameter toward ranking in the decision-making process. Thus, the proposed model offers an alternative, user-friendly method that is reliable in terms of patients and practicing decision.